Mi mama - Alexander, Francie; Cervantes, Jesus P.; Bernales, Carlos E. (New York : Scholastic, 1998)
A girl tells of her mother loves her, her brother, and their cat and how they all love mother in return. Words which will give readers practice using the letter "m" in are used in the story.
In Spanish.
Keywords: Mothers -- Juvenile fiction; Mother and child -- Juvenile fiction; Cats -- Juvenile fiction; Reading -- Phonetic method; Spanish language materials